2015
DOI: 10.1097/rlu.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Early Assessment of Metabolic Response by 18F-FDG PET During Concomitant Radiochemotherapy of Non–Small Cell Lung Carcinoma Is Associated With Survival

Abstract: Early assessment of TLG response by 18F-FDG PET/CT during concomitant radiochemotherapy of non-small cell lung cancer might be associated with survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Several investigations are being conducted on the role of change in MTV and TLG as an early predictor of therapy response. [34][35][36][37] Thus, these metrics could provide useful measures of response in response-adaptive therapy regimens. However, for these metrics to be incorporated as a routine predictive biomarker, a PET segmentation methodology that yields precise values of these metrics is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations are being conducted on the role of change in MTV and TLG as an early predictor of therapy response. [34][35][36][37] Thus, these metrics could provide useful measures of response in response-adaptive therapy regimens. However, for these metrics to be incorporated as a routine predictive biomarker, a PET segmentation methodology that yields precise values of these metrics is needed.…”
Section: Discussionmentioning
confidence: 99%
“…That study also indicated the potential use of during‐RT 18 F‐FDG PET in early treatment response assessment by showing significant correlation of 18 F‐FDG reduction of the primary tumors and lymph nodes between during‐ and post‐RT 18 F‐FDG PET scans. Subsequent studies supported the application of during‐RT 18 F‐FDG PET in predicting treatment outcomes of NSCLC patients . But these studies were either retrospective in nature or lacked comparisons of serial 18 F‐FDG PET scans.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that preoperative staging PET/CT leads to change in the treatment planning and reduces the frequency of futile thoracotomies and the total number of thoracotomies (6,7). PET-based quantitative parameters have been proposed as reliable indicators of survival in patients with lung cancer in both pretreatment and posttreatment settings (8)(9)(10)(11)(12). In the posttherapy setting, several studies point to the usefulness of monitoring the treatment response based on decreased SUVs on serial 18 F-FDG PET imaging of the primary tumor (4,8).…”
mentioning
confidence: 99%